Roinnt Scéalta: some stories about Irish people - Colton, Gavin (Kansas State University, 2018)
Fintan O’Toole proposes that Irish modernist writers could afford to be “opaque, allusive, densely textured” (410). Contrastingly, he posits that contemporary Irish writers, who engage in the simple ritual of words, believe that “the accumulation of potent and precise detail, if it is sufficiently thoroughly imagined, will call the universe into being” (412). The later microcosmic approach to storytelling has the power to speak to the same philosophical ideas, falling away from “the high ambition of Irish modernism” (412). “Roinnt Scéalta: Some Stories about Irish People” examines financial globalization and social progress in Ireland through careful observation of daily life, simple fragments of Irish characters’ lives, stripped-down to small moments that stand for larger public truths: Irish wives still want holidays to Europe, Irish men still wish to gamble and be independent of authority in their work, young adults still emigrate to America. Yet there are new truths: Black children speak Irish in Gael scoils, children of Polish and Chinese immigrants play hurling and Gaelic football in Croke Park, and African men set up window-washing services in small Irish towns. These stories evoke the voices of the displaced to convey the ways in which Ireland is shifting, socially and economically: Frank has lost his job as a painter, and the strain it causes on his marriage forces him into a job for a large corporation; Peo, having demolished his way through Dublin to pave space for apartments he could never afford and businesses he would never patron, finds work providing simple comfort to Buffalo, who is at the mercy of state-supported healthcare and monthly welfare checks; Iarla is convinced by Seán that moving to America will remedy his sense of deflation toward the Irish job market. While the progression of social norms is queried in these stories, they still reinforce and embody many of the sweeping generalizations associated with Irish fiction. This collection delves into the minds and morals of the displaced Irish working class, focusing oftentimes on the pub and the inner-workings of local, social politics in a fictional small town on the skirt of Dublin’s southside.
Keywords: Ireland; Short Story; Post-colonial; Pre-colonial; Financial Globalization; Masculinity